Polish minority in Ukraine. Memories (Discourse of Law and Administration, 2019)
The Polish minority in the Ukraine has since time immemorial appeared. The first Poles already arrived at this land in the 14th century with the of civilization mission. Their fate in the neighbouring country was diversified. At first they were pleased with a respect and numerous privileges. A coming into existence worsened Polish-Ukrainian relationships by B. Chmielnicki uprising caused by the pressure of Cossacks by Polish magnates. In 1925 for Poles, inhabited in the Soviet Ukraine an autonomous called region was created Marchlewszczyzną. From the time of the World War II, repressions and persecution affected them. The Polish minority was recognised behind the obstacle to creating the state of the Ukrainian. In 1944 they committed the brutal murder on Poles settling west of Ukraine (60 thousand persons were butchered), in order to this soil were assigned to Ukraine rather than Poland after the war . Poles were also being victimised in Lvov, forcing them to the trip to the country of origin. The ones which stayed, lived in the constant intimidation, concealing their Polish identity. Inasmuch as before the war, in the Ukraine 500 thousand of the Polish minority lived, at present this minority is getting smaller what is resulting: mixed marriages, broadcasting Ukrainian or Russian name Polish children, migration from the village for cities, lack of the ability of using Polish, emigration of members of minorities to Poland, of considerable dispersion, hampering integration, period of population decline, peeling off from the Roman Catholic Church, being the last anchor of the Polish national identity in the East and neglecting from the side states of the origin. According to estimated data in the Ukraine today 144.1 lives thousand of Poles.
Keywords: history of Poles in Ukraine; Poles in Lviv; Assimilation of Poles; Ukrainianisation of the Catholic church; Polish associations